1993
DOI: 10.1161/01.res.72.3.658
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet-activating factor in hypotension and platelet activation induced by infusion of thrombolytic agents in rabbits.

Abstract: Infusion of the thrombolytic agents streptokinase (SK, 666 units/kg per minute for 60 minutes) and tissue-type plasminogen activator (t-PA, 10 micrograms/kg per minute for 15 minutes) in rabbits induced a significant hypotension and decrease in platelet count that were completely prevented by treatment with platelet-activating factor (PAF) receptor antagonists SDZ 63-675 and WEB 2170. PAF synthesis by vascular tissue was suggested by its extraction from blood-free heart and aorta of rabbits treated in vivo wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Hearts of group 4 (n ϭ 5) underwent a preconditioning protocol like group 2 hearts, bracketed by a 29-min infusion of the PAF receptor antagonist WEB-2170 (1 ϫ 10 Ϫ9 M; Boheringer Ingelheim), a triazolobenzodiazepine derivative (4,16,27,31). To test the role of the used antagonists per se on I/R damages, in three additional groups of hearts (n ϭ 5 for each group), the antagonists WEB-2170 (group 8), chelerythrine (group 9), or LY-294002 (group 10) were infused for 29 min without PAF and IP.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Hearts of group 4 (n ϭ 5) underwent a preconditioning protocol like group 2 hearts, bracketed by a 29-min infusion of the PAF receptor antagonist WEB-2170 (1 ϫ 10 Ϫ9 M; Boheringer Ingelheim), a triazolobenzodiazepine derivative (4,16,27,31). To test the role of the used antagonists per se on I/R damages, in three additional groups of hearts (n ϭ 5 for each group), the antagonists WEB-2170 (group 8), chelerythrine (group 9), or LY-294002 (group 10) were infused for 29 min without PAF and IP.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…This may depend on the production of thromboxane A2, as suggested by Fitzgerald et al'0 In fact, it has recently been shown that thromboxane A2 mediates and amplifies in vivo many of the biological effects of PAF.58 Experiments performed in rabbits infused with SK and t-PA demonstrated that early thrombocytopenia is PAF dependent and can be prevented by treatment with PAF receptor antagonists. 30 In addition, a local synthesis of PAF and its association with the EC surface may induce platelet/ endothelium and polymorphonuclear neutrophil/endothelium interaction, thus favoring thrombotic reocclusion.31-33 The possible role of PAF in determining thrombotic reocclusion is also supported by experiments performed in dogs, showing that oral administration of a PAF-receptor inhibitor completely prevented reocclusion of femoral arteries after thrombolysis.59 Conversely, the negative effect of PAF may be modulated by the production of prostacyclin, which may inhibit both the synthesis of PAF and its bioactivity.42 It has been reported that whereas thrombolytic agents stimulated the synthesis of prostacyclin,60 plasmin has a potent inhibitory effect on it.61 In conclusion, the beneficial effect of thrombolytic therapy may be limited by production of endogenous mediators, including PAF, that may activate platelets locally and in systemic circulation and that may exert a direct negative inotropic and arrhythmogenic effect.l1820,22,25-27A6 The present results should stimulate further studies intended to determine whether patients with acute myocardial infarction undergoing thrombolytic therapy may benefit from concomitant treatment with PAF-receptor antagonists.…”
Section: Patientsmentioning
confidence: 99%
“…29 The observation that in rabbits treated with thrombolytic agents, PAF-receptor antagonists prevented the activation of platelets prompted us to hypothesize that PAF synthesis induced by thrombolytic agents may promote the activation of platelets. 30 The local generation of PAF and its association with endothelial cell (EC) surface may lead to platelet and/or leukocyte/endothelium interaction,31-33 thus favoring reocclusion. In the present investigation, we evaluated (1) the intravascular release of PAF in patients with acute myocardial infarction treated or untreated with intravenous SK and (2) the synthesis of PAF by cultured human umbilical vein-derived endothelial cells (ECs) challenged with SK, tissue-type plasminogen activator (t-PA), or plasmin.…”
mentioning
confidence: 99%
“…Platelet-activating factor (PAF), a phospholipid mediator involved in the regulation of inflammation, thrombosis, atherogenesis and cardiovascular function (Bussolino et al, 1989;Montrucchio et al, 1993;Subbanagounder et al, 1999;Montrucchio et al, 2000;Zimmerman et al, 2002;Haynes, et al, 2002;Goggel et al, 2004), is released from erythrocyte progenitor cells upon increase of cytosolic Ca 2+ activity (Dupuis et al, 1997). PAF further activates Ca 2+ -sensitive K + channels (Gardos channels) in the erythrocyte cell membrane (Garay et al, 1986) by sensitising them for the stimulating effects of cytosolic Ca 2+ (Rivera et al, 2002).…”
Section: Introductionmentioning
confidence: 99%